Prevalence of individual brain and eye defects potentially related to Zika virus in pregnancy in 22 U.S. states and territories, January 2016 to June 2017. Issue 14 (30th July 2022) - Delaney, Augustina; Olson, Samantha M.; Roth, Nicole M.; Cragan, Janet D.; Godfred‐Cato, Shana; Smoots, Ashley N.; Fornoff, Jane; Nestoridi, Eirini; Eckert, Valorie; Forkner, Allison; Stolz, Amanda; Crawford, Katherine; et al.
Abstract: During the Centers for Disease Control and Prevention's Zika Virus Response, birth defects surveillance programs adapted to monitor birth defects potentially related to Zika virus (ZIKV) infection during pregnancy. Pregnancy outcomes occurring during January 2016 to June 2017 in 22 U.S. states and territories were used to estimate the prevalence of those brain and eye defects potentially related to ZIKV. Jurisdictions were divided into three groups: areas with widespread ZIKV transmission, areas with limited local ZIKV transmission, and areas without local ZIKV transmission. Prevalence estimates for selected brain and eye defects and microcephaly per 10, 000 live births were estimated. Prevalence ratios (PRs) and 95% confidence intervals (CIs) were estimated using Poisson regression for areas with widespread and limited ZIKV transmission compared with areas without local ZIKV transmission. Defects with significantly higher prevalence in areas of widespread transmission were pooled, and PRs were calculated by quarter, comparing subsequent quarters to the first quarter (January–March 2016). Nine defects had significantly higher prevalence in areas of widespread transmission. The highest PRs were seen in intracranial calcifications (PR = 12.6, 95% CI [7.4, 21.3]), chorioretinal abnormalities (12.5 [7.1, 22.3]), brainstem abnormalities (9.3 [4.7, 18.4]), and cerebral/cortical atrophy (6.7 [4.2, 10.8]). The PR of the nine pooled defects was significantly higher in three quarters in areas with widespread transmission. The largest difference in prevalence was observed for defects consistently reported in infants with congenital ZIKV infection. Birth defects surveillance programs could consider monitoring a subset of birth defects potentially related to ZIKV in pregnancy.